PERANCANGAN PEMBANGKIT TENAGA LISTRIK TENAGA SURYA DENGAN PANEL SURYA MONOCRYSTALLINE 60 WP - Imam Wahidin; Rahmat Hidayat (Jurnal Ilmiah Wahana Pendidikan, 2023)
Solar energy (solar) provides many benefits for lifeman. One of the utilization of solar energy that can be implementedis in the form of a Solar Power Plant (PLTS). OnIn this design, a solar cell electric power system will be designedwith a capacity of 60 WP and 12 V battery Power system performanceThis monocrystalline solar cell has a power of 60 WPlater it will be connected to a battery of 12 V and a current of 5 Ahto be used as an energy source in garden huts aslighting at night and during the day to charge the batteryassuming this 60 WP will fulfill the batteryused, this can be useful for the distance between the house and the rice fieldswhich is far away and requires electrical energy this design is expectedbeneficial to society and socially as well as used asmodel for developing a network of Power Electricity SystemsSolar (PLTS)